Pengaruh Citra Merek, Relationship Marketing, dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan pada E-Commerce Shopee di Kota Batam - Nanda Adelia Putri Sitorus; Tiurniari Purba (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study aims to determine the effect of brand image, relationship marketing, and customer satisfaction on customer loyalty in Shopee e-commerce users in Batam City. This research used quantitative methods with descriptive and causality approaches. Data collection was conducted through questionnaires distributed to 100 Shopee users in Batam City. Data analysis techniques used multiple linear regression analysis with IBM SPSS version 27. The results showed that brand image had a positive and significant effect on customer loyalty with a t-value of 3.142 and a significance value of 0.002. Relationship marketing had a positive and significant effect on customer loyalty with a t-value of 2.874 and a significance value of 0.005. Customer satisfaction had a positive and significant effect on customer loyalty with a t-value of 4.281 and a significance value of 0.000. Simultaneously, brand image, relationship marketing, and customer satisfaction had a positive and significant effect on customer loyalty with an F-value of 58.327 and a significance value of 0.000. The Adjusted R Square value of 0.635 indicates that customer loyalty can be explained by 63.5% through the independent variables in this study.